Report from the fifth international consensus meeting to harmonize core outcome measures for atopic eczema/dermatitis clinical trials (HOME initiative). (1st May 2018) - Chalmers, J.R.; Thomas, K.S.; Apfelbacher, C.; Williams, H.C.; Prinsen, C.A.; Spuls, P.I.; Simpson, E.; Gerbens, L.A.A.; Boers, M.; Barbarot, S.; Stalder, J.F.; Abuabara, K.; et al.
Summary: This is the report from the fifth meeting of the Harmonising Outcome Measures for Eczema initiative (HOME V). The meeting was held on 12–14 June 2017 in Nantes, France, with 81 participants. The main aims of the meeting were (i) to achieve consensus over the definition of the core domain of long‐term control and how to measure it and (ii) to prioritize future areas of research for the measurement of the core domain of quality of life (QoL) in children. Moderated whole‐group and small‐group consensus discussions were informed by presentations of qualitative studies, systematic reviews and validation studies. Small‐group allocations were performed a priori to ensure that each group included different stakeholders from a variety of geographical regions. Anonymous whole‐group voting was carried out using handheld electronic voting pads according to predefined consensus rules. It was agreed by consensus that the long‐term control domain should include signs, symptoms, quality of life and a patient global instrument. The group agreed that itch intensity should be measured when assessing long‐term control of eczema in addition to the frequency of itch captured by the symptoms domain. There was no recommendation of an instrument for the core outcome domain of quality of life in children, but existing instruments were assessed for face validity and feasibility, and future work that will facilitate the recommendation of an instrument was agreed upon.